(untitled) (Research, Society and Development, 2021)
The sugarcane planting operations are the ones that require greater care, as the mistakes made at that time cause losses for all crop cycles. Therefore, the objective of the work was to evaluate the quality of the semi-mechanized planting of sugarcane through the furrow carried out by 2 tractors and 2 varieties of sugarcane, using the Statistical Process Control (CEP). The study was carried out in the experimental area in partnership with IF Goiano - Campus Ceres and Usina CRV. The experimental design used was a complete randomized design, with 4 treatments, composed of 2 varieties of sugar cane and 2 tractors with a two-row furrow implement equipped with an autopilot, with 15 repetitions per treatment. The variables analyzed were: depth and width of furrow, parallelism between furrows, height of covering, number and length of grinding wheels, total, viable and non-viable buds, number of tillers, sprouting failures, plant height and diameter of thatch. The results were discovered by descriptive statistical analysis and analysis of variance by statistical process control. For furrow-related variables, the fleet tractor 42 results in better results. As for the varieties, the SP80-1816 stood out, along with the left 41 furrow tractor for variables aimed at distribution, service and agronomic indexes. The variability of the variables was high, and it is recommended that the plant have the best control so that the planting has the best final quality.